INVOLVEMENT OF TUBERCULOUS MENINGITIS PATIENT WITH HOSPITAL ACQUIRED PNEUMONIAE: Case Report - Pakpahan, Edwin Anto; Alamsyah, Raja Iqbal; Hermanto, Tsaniya Difa; Helminta Nst., Reyhan Khaira; Mahardika, Virani; Daulay, Kanina Hatia Putri (Majalah Ilmiah METHODA, 2024)
Meningitis is a global public health problem. The causes can be viruses, bacteria, fungi and parasites. Meningitis is an infectious disease that cannot be overcome and is still a problem in developing countries. As a developing country Indonesia, Tuberculosis has a high number of cases throughout the year. Tuberculous meningitis (TB) is an infection byMycobacterium tuberculosisabout meningor brain parenchyma resulting variety morbidity and mortality. A 39 years old woman came to the emergency room at Drs. H. Amri Tambunan complained of seizures 1 day ago with a duration of more than 1 hour. Seizures are found throughout the body. Also a fever was found 1 day today. Shortness of breath and cough were found for the past 3 days. Decreased appetite has been observed for the past 1 week. There was no history of nausea and vomiting. Os post VP shunt installation on May 29th, 2023. Female patient, 39 years old, with a diagnosis of Tuberculous Meningitis with Hospital Acquired Pneumoniae has been hospitalized from 9 to 20 September of 2023. And also outpatient treatment at the Pulmonology Departement is recommended.